Trends in victimization in schools and elsewhere, 1974–1981 - Parker, Robert Nash (Journal of quantitative criminology, 1991)
Trends in the rate of victimizations of juveniles in three settings-schools, homes, and streets/parks-are examined monthly during the period 1974–1981. The relationship between in-school victimization rates and those occurring outside of school are analyzed with multivariate ARMA models informed by previous research on school victimization (Gottfredson and Gottfredson, 1985) and an importation perspective on the source of crime and victimization in institutions such as schools. Results indicate that the overall in-school victimization rate remained relatively stable during this period but that victimization rates of juveniles in other settings had significant effects on in-school victimizations. This suggests that underlying causes of victimization in general are important determinants of victimization in schools. These results are limited, however, as we examine these sources of victimization only indirectly via relationships among the different victimization rates in dynamic models and by the aggregate nature of the monthly data from the National Crime Survey.